PENGUATAN ANALISIS HUKUM PERJANJIAN KREDIT PEMILIKAN RUMAH (KPR) DI INDONESIA - Nasution, Chairuni (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
Banking is one of the sources of obtaining funds that are considered easy and fast for some people in terms of meeting their needs, such as in the use of funding from banks with the Home Ownership Credit facility. The existence of the Home Ownership Credit system is very much needed by people whose economic income is in the small and medium level where in this case the credit granting process, rights, and obligations will arise. so that the Bank can only consider extending credit if the applicant is a legal subject, because the legal subject is a proponent of rights and obligations, meaning that it can receive rights and incur obligations. The purpose of this research is to find out the legal arrangements in the Home Ownership Credit, to determine the rights and obligations of the parties in the Home Ownership Credit agreement, and to determine efforts to resolve wan achievements in the Home Ownership Credit agreement. This research is normative, namely research that refers to the legal norms that can be in the laws and regulations as well as existing legal norms. in society, using a qualitative research type. This research was obtained from secondary data, namely literature study, namely by collecting references related to the object or research material. The data obtained from the research will then be used as a reference in conducting analysis and problem-solving. To process existing data, this study used a qualitative analysis method